Doing feminist physical cultural research in digital spaces: reflections, learnings and ways forward. Issue 1 (2nd January 2021) - Toffoletti, Kim; Olive, Rebecca; Thorpe, Holly; Pavlidis, Adele
ABSTRACT: In this article we draw on our varied experiences of conducting feminist sport and leisure scholarship in digital spaces to offer some reflections, learnings and ways forward for navigating the challenges of digital and social media research. The paper outlines our methodological and ethical relationships to doing feminist research with and about women and girls, taking Margaret McClaren's activist lens as a starting point to consider issues of positionality and reflexivity when researching lived experiences of gender in digital spaces. We then analyse our own actions across four dimensions of the research process: (1) connecting with communities and participants, (2) conceptualising and managing data, (3) navigating the ethics of representation and (4) vulnerabilities and self-care. In sharing our learnings from a range of projects, this paper offers insights into the methodological implications of conducting digital research on the moving body, as well as practical considerations for those doing feminist research on sporting and physical cultures in digital spaces. This article contributes to emerging conversations amongst qualitative sport and physical activity researchers about the challenges of digitisation for feminist engagements with power, context and situated knowledges.